Standardisasi Nisab Zakat Penghasilan dalam SK Baznas No. 15 Tahun 2026: Analisis Fragmentasi Ijtihad Ulama dan Ketegangan Maqāṣid Al-Syarī‘ah - Desi Yusdian; al ikhlas; Ahmad Salman Farid; Fathurrahmi Fathurrahmi (Jurnal Hukum Lex Generalis, 2026)
This study examines the controversy over the standardization of income zakat in Decree No. 15 of 2026 with a focus on the differences in the ijtihad of ulama in the determination of nisab. The absence of explicit nash opens up the space of ijtihad and produces various approaches. This study aims to analyze the pattern of ijtihad, the dominance of regulatory authorities and its implications in the perspective of maqāṣid al-syarī'ah. The method used is qualitative through literature studies with content and comparative analysis. The results show 3 (three) findings: the fragmentation of ijtihad (gold, agriculture, hybrids), the shift of authority from fiqh to regulation and the tension between standardization and flexibility of maqāṣid al-syarī'ah. Standardization is seen as an institutional ijtihad that needs to be balanced in order to maintain normative legitimacy.